Reading Assessment from a Whole Language Perspective - Woodley, John W. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
Several approaches to reading assessment, based on the whole language approach, can provide teachers with a frame of reference to guide them in making decisions about selecting and planning classroom activities. The more traditional approach to reading assessment, usually referred to as reading diagnosis, focuses on the final product (the test scores) and looks for symptoms of underlying reading disorders. Whole language is a theoretical perspective which allows both teachers and students to focus on growth and development in language use and language learning rather than on instruction, conformity or a fixed curriculum. Approaches to reading assessment within the whole language framework include a print awareness task, book handling task, patterned language task, reading interview, miscue analysis, and situational responses to reading. The observations made by teachers using these assessments provide a meaningful alternative to heavy reliance on standardized tests and lead to a more effective educational program for all. (Twelve references are attached.) (RS)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Class Activities; Classroom Observation Techniques; Classroom Techniques; Elementary Education; Informal Reading Inventories; Reading Achievement; Reading Comprehension; Reading Diagnosis; Whole Language Approach; Guides, Classroom -- Teacher